Serum induces transcription of Hey1 and Hey2 genes by Alk1 but not Notch signaling in endothelial cells - Wöltje, Kerstin; Jabs, Markus; Fischer, Andreas (PLOS ONE, 2015)
The transcriptional repressors Hey1 and Hey2 are primary target genes of Notch signaling in the cardiovascular system and induction of Hey gene expression is often interpreted as activation of Notch signaling. Here we report that treatment of primary human endothelial cells with serum or fresh growth medium led to a strong wave of Hey1 and Hey2 transcription lasting for approximately three hours. Transcription of other Notch target genes (Hes1, Hes5, ephrinB2, Dll4) was however not induced by serum in endothelial cells. Gamma secretase inhibition or expression of dominant-negative MAML1 did not prevent the induction of Hey genes indicating that canonical Notch signaling is dispensable. Pretreatment with soluble BMP receptor Alk1, but not Alk3, abolished Hey gene induction by serum. Consequently, the Alk1 ligand BMP9 stimulated Hey gene induction in endothelial cells. Several other cell types however did not show such a strong BMP signaling and consequently only a very mild induction of Hey genes. Taken together, the experiments revealed that bone morphogenic proteins within the serum of cell culture medium are potent inducers of endothelial Hey1 and Hey2 gene expression within the first few hours after medium change.
Gesehen am 18.10.2017